Application of Problem Based Learning (PBL) Learning Model To Increase Science Learning Outcomes - Febrianti, Wulan Eka (Universitas Sebelas Maret, 2020)
This study purpose to improve learning outcomes in Science about the solar system in grade IV students of SDN Malahayu 03 Banjarharjo, District, 2019/2020 academic year. This study uses a Classroom Action Research (CAR) model which is carried out in 2 cycles. The results showed that there was an increase in student learning outcomes using the Problem Based Learning (PBL) learning model. In the pre-cycle stage of 22 students who achieved learning completeness 5 students (23%). Then in the first cycle of learning completeness reached 13 students (59%) and in the second cycle there was an increase to 20 students (91%). So the conclusion of this study shows that learning with the the Problem Based Learning (PBL) learning model improves science learning outcomes about the solar system in grade IV students of SDN Malahayu 03, Banjarharjo District, semester I of the 2019/2020 school year.